POLA KOMUNIKASI KELUARGA DALAM MENGHADAPI ANAK DISABILITAS KORBAN BULLYING - Akbar Panigraha; Marfuah Sanityastuti (Jurnal Humanitaria Jurnal Ilmu Sosial dan Humaniora, 2026)
Bullying is a form of violence that is very detrimental to an individual, where the victim gets bad treatment from the perpetrator who considers himself to have the power and power to be able to do anything to him because he is considered helpless. One of the characteristics of victims who often get bullying treatment  occurs in children with special needs or disabilities. The importance of family communication patterns is what can minimize the impact that occurs due to bullying  treatment. This study aims to determine how family communication patterns in dealing with children with disabilities victims  of bullying carried out by families of SLB Negeri 1 Bantul students. The research method used is a qualitative research method with a case study approach. The results showed that family communication patterns carried out on children with disabilities with different family backgrounds were also very diverse in applying communication to victims, when facing the impact that occurred. Like there are those who apply high to low conversation orientation and also some who apply high to low conformity orientation. However, not all families apply the family communication pattern well. Due to limited knowledge related to this. Of course, this adjusts to the conditions and circumstances of the victim in carrying out his approach. One of them pays attention to the side of the impact that occurs, both direct and indirect impacts on victims.